THE ERROR ANALYSIS OF SPEAKING SKILL ON THE SIXTH SEMESTER ENGLISH EDUCATION STUDENTS AT INDO GLOBAL MANDIRI UNIVERSITY - Rika Pratiwi; Nike Angraini; Rudi Hartono (Global Expert: Jurnal Bahasa dan Sastra, 2022)
This research aimed at finding out the types of error based on Surface Strategy Taxonomy (Dulay, Burt, and Krashen, 1982) that found at ELT student’s speaking and analyzing some factors influencing their errors. The subject of this research was the sixth semester students of English Education from Indo Global Mandiri University who already taken speaking 3 and structure 4 courses. Qualitative study was used as a method to obtain the data. The data was taken from final exam video of speaking 3 course. The researcher analyzed the data following the Error Analysis (EA) procedures which involves transcribing, coding, classifying error, also explaining the errors and their factors. The result shows that the most dominant error were omission (55,50%), followed by addition (22,49%), misformation (18,66%), and misordering (3,35%). The current research investigated the factor of errors based on their source were intralingual and interlingual interference. Meanwhile, intralingual was considered as the major cause of the students’ errors. In conclution, the students still have a problem in terms of grammatical aspect of their speaking. It is suggested that the students should pay more attention to the grammatical aspect and improve their speaking skills.